Assessing the Quality of Life of Parents of Children With Disabilities Using WHOQoL BREF During COVID-19 Pandemic - Ali, Usman; Bharuchi, Vardah; Ali, Nasreen Gulzar; Jafri, Sidra K. (Frontiers in Rehabilitation Sciences, 2021)
Background Caring for a child with disability is a challenging journey as these parents must meet greater demands when compared to parents of typically developed children. Looking after a child with disability requires additional financial, social, emotional and physical resources. Coronavirus 2019 (COVID -19) has made it more challenging to meet such demands. Methods In all 301 parents of children between the age range of 2 years and 18 years were allocated for the study through convenient sampling at a tertiary hospital. Two groups of parents were identified: parents of typical and atypical children with 151 in group of parents with typically developing and 150 in the group of parents of children with disabilities. The study was an analytical cross-sectional design with a comparison group. The Urdu version of World Health Organization Quality of Life Measure Abbreviated version (WHO-QOL BREF) (Lodhi et al., 2017) was used to measure the quality of life (QOL) among parents. Sociodemographic data was also obtained from the parents. Results Parents of children with disabilities scored lower overall when different domains of quality of life were considered (physical health, psychological health, social relationships, and environment) using WHO-Quality of Life (QoL)BREF. Statistically significant differences were observed in the physical and environmental domains of parental QoL.